Review Tentang Sumber dan Dampak Pencemaran Laut - AZIZ DANISWARA; GALUH RETNO CAHYANINGNUGROHO; HELEN QURROTU AINI (Prosiding ESEC, 2023)
Marine pollution is one of the national and international issues that the entry of dangerous substances due to human activities into the marine environments, therefore it will cause problems in changing ecosystems on the sea. Marine pollution can result from the disposal of domestic waste, industrial waste, radioactive substances, ship loading and unloading activities, and mineral mining offshore. The impact of pollution will disrupt the aquatic ecosystem, environmental quality, and environmental aesthetics. The international conventions for controlling marine pollution at the international level, that is International Maritime Organization (IMO) produce agreements to overcome pollution issues that occur due to oil spills and dangerous toxic goods which require preparation and action response to oil pollution in various forms, which threaten environmental sustainability maritime.